Making pictures and patterns - Mell, Howard; Fisher, Eric (New York, Drake Publishers, 1971)
Instructions for creating collages, rubbings, chalk and crayon transfers, see-through patterns, and paintings.
Keywords: Handicraft -- Juvenile literature; Art -- Juvenile literature; Handicraft; Art